KEANEKARAGAMAN JENIS POHON FAMILI DIPTEROCARPACEAE DI HUTAN ADAT BUKIT BENUAH KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA - Septria, Devie; Manurung, Togar F; Tavita, Gusti Eva (JURNAL HUTAN LESTARI, 2018)
Dipterocarpaceae is a group of pantropic plants which members are widely used in the timber field. Due to much exploitation, several important members of this tribe have entered the IUCN Red List as an endangered species. This study aims to obtain data information about the diversity of Dipterocarpaceae family tree species in the indigenous forest of Bukit Benuah Sungai Ambawang sub-district, Kubu Raya regency. The research method used in the analysis of vegetation in the field using survey method with a combination of tracks and lines technical in the track by placing the track of observation through the purposive sampling approach. The tracks used in the field are 8 paths with 76 plots of land in the observation area of 270.63 Ha. Based on research conducted in indigenous forest of Bukit Benuah Sungai Ambawang subdistrict, Kubu Raya regency, found 41 tree species from 430 individual tree level obtained during the research. Vegetation of 41 species is a recapitulation of 22 families and 34 genus. The species compositions found in indigenous forest Bukit Benuah are mostly dominated by trees with Dipterocarpaceae family with 125 individual trees. Dipterocarpaceae which is the dominated family has 5 genus including Dryobalanops, Dipterocarpus, Hopea, Shorea, and Vatica.Keywords: Dipterocarpaceae, Indigenous Forest, The Diversity